Museum Musik Indonesia sebagai Wisata Edukasi di Kota Malang - Moch. Nurfahrul Lukmanul Khakim (Jurnal Pendidikan Sejarah, 2019)
Malang as a city with many tourist destinations, has advantages in every field of tourism. Of the many tourist destinations, research on museums is very rare, even though museums can be interesting educational facilities for students or the general public. One of the museums in Malang City is the Indonesian Music Museum, this museum is relatively new so it is interesting to study. This museum has 26000 music collections. The details, as many as 16,718 are cassettes; 3,118 compact discs (CDs); 3,108 printed materials such as posters, books and leaflets; 2,985 LPs; 108 musical instruments (guitars, drums, etc.); 55 artist clothes; and 13 audio equipment. The Indonesian Music Museum can be used as an educational tour for the people of Malang to get to know the history of music in Indonesia. In addition, the potential to become one of the leading tours in Malang City is very open as long as it is done with active and attractive promotions. Malang sebagai salah satu kota dengan destinasi wisata yang cukup banyak, mempunyai keunggulan dalam setiap bidang wisata. Dari sekian banyak destinasi wisata tersebut, penelitian tentang museum sangat jarang, padahal museum bisa menjadi sarana edukasi yang menarik untuk para pelajar ataupun masyarakat umum. Salah satu museum yang ada di Kota Malang adalah Museum Musik Indonesia, museum ini tergolong baru sehingga menarik untuk diteliti. Museum ini memiliki 26000 koleksi musik. Rinciannya, sebanyak 16.718 adalah kaset; 3.118 buah compact disc (CD); 3.108 barang cetakan seperti poster, buku, dan leaflet; 2.985 piringan hitam; 108 instrumen musik (gitar, drum, dan lain-lain); 55 baju artis; dan 13 peralatan audio. Museum Musik Indonesia dapat dijadikan sebagai wisata edukasi bagi masyarakat Malang untuk mengenal sejarah musik di Indonesia. Selain itu potensi untuk menjadi salah satu wisata unggulan di Kota Malang sangat terbuka luas asalkan dilakukan dengan promosi yang giat dan menarik.